(untitled) (Journal Of Educational and Psychological Researches, 2012)
Whereas conventional methods of teaching history do not meet the sometimes purpose has suggested some educators strategies modern help to improve the level of students in the education process through activating prior knowledge and employed in positions of current learning, and focus attention on the points and the outstanding elements of the content and practice techniques Calendar criticof ideas and meanings and mental and linguistic activities used to verify the extent of reaching understanding. So targeted Current search to know (KWL strategy effectiveness in the collection of fourth-grade students of history literary and the development of cognitive thinking skills they have) and to identify the impact researcher developed the following null hypotheses: 1 - There are a statistically significant difference at the level of significance (0.5) between the average collection of experimental group students taught according kwl strategy and the average collection of control group students taught in the traditional way in the post achievement test. 2 - There are a statistically significant difference at the level of significance (0.5) between the average scores of the experimental group students and taught according to kwl strategy and the average degrees of control group students taught according to the traditional method of testing cognitive thinking skills. 3 - There are a statistically significant difference at the level of significance (0.05) between the average scores of students in the experimental group cognitive thinking skills test pre and post. 4 - There are a statistically significant difference at the level of significance (0.05) between the average scores of control group students in cognitive thinking skills test pre and post. To investigate, the researcher has chosen the design of the control group with pre and post test in cognitive thinking skills, and post in the collection, and was elected to be purposive sample of fourth-grade students in junior high literary Muthanna General Directorate for Education Baghdad / Rusafa first. The sample search (70) students, by (35) students per group, between two sets of students rewarded Search variables (academic achievement, intelligence, prior knowledge, cognitive thinking tribal). Researcher prepared (52) target behaviorally covered first and second chapter of the material Arab history Islamic, and made ​​plans teaching of subjects selected for the experiment, and to measure the collection of students Group Search at the end of the experiment, which lasted (12) weeks, researcher prepared a test included (30)paragraph of multiple choice type, has been characterized by honesty and reliability testing. Also prepared test cognitive thinking skills included (38) paragraph of multiple choice type, characterized by honesty and consistency. After analyzing the results statistically, came on as follows: 1 - outweigh the experimental group and studied according kwl strategy on the control group, which studied according to the traditional method of dimensional achievement test. 2 - than the experimental group which studied according kwl strategy on the control group, which studied according to the traditional method of testing cognitive thinking skills. 3 - The presence of a statistically significant difference between pre and post tests and in favor of the post among students in the experimental group. 4 - There are a statistically significant difference between pre and post tests among students in the control group. The study came out a number of recommendations and suggestions.